2021
DOI: 10.1021/acs.jmedchem.1c01491
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Indenoisoquinolines Targeting Topoisomerase I and Other Biological Macromolecules for Cancer Chemotherapy

Abstract: The discovery that certain indenoisoquinolines inhibit the religation reaction of DNA in the topoisomerase I-DNA-indenoisoquinoline ternary complex led to a structure-based drug design research program which resulted in three representatives that entered Phase I clinical trials in cancer patients at the National Cancer Institute. This has stimulated a great deal of interest in the design and execution of new synthetic pathways for indenoisoquinoline production. More recently, modulation of the substitution pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 135 publications
(474 reference statements)
0
7
0
Order By: Relevance
“…Pharmaceutically relevant indeno­[1,2- c ]­isoquinolin-11-one and indeno­[1,2- c ]­isoquinoline-5,11-dione derivatives ( 5a–c ) were synthesized efficiently in the COware-RB setup through the carbonylative Suzuki–Miyaura coupling of C-4 iodo-derivatives of isoquinolines and isoquinolones with o -bromophenylboronic acid followed by site-selective C-3 cyclization (Scheme ). It is noteworthy that although several synthetic multistep procedures have been reported in the literature that furnish such topoisomerase inhibitors, employing the “Chloroform-COware” technique facilitated by the COware-RB arrangement has allowed the facile sequential one-pot synthesis of such privileged motifs.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmaceutically relevant indeno­[1,2- c ]­isoquinolin-11-one and indeno­[1,2- c ]­isoquinoline-5,11-dione derivatives ( 5a–c ) were synthesized efficiently in the COware-RB setup through the carbonylative Suzuki–Miyaura coupling of C-4 iodo-derivatives of isoquinolines and isoquinolones with o -bromophenylboronic acid followed by site-selective C-3 cyclization (Scheme ). It is noteworthy that although several synthetic multistep procedures have been reported in the literature that furnish such topoisomerase inhibitors, employing the “Chloroform-COware” technique facilitated by the COware-RB arrangement has allowed the facile sequential one-pot synthesis of such privileged motifs.…”
Section: Resultsmentioning
confidence: 99%
“…Cushman and other researchers reacted imines ( 132 ) and differently substituted homophthalic anhydrides ( 133 ) to prepare cis -substituted isoquinolones ( 134 ) that were treated with thionyl chloride to yield indenoisoquinolines ( 135 ; Scheme 43 ) [ 81 , 82 , 83 ]. A large number of indenoisoquinolines ( 135 ) were prepared and screened as inhibitors of topoisomerases and ligands for other biomolecules, providing valuable information to understand and modulate their biological activity [ 32 ].…”
Section: Two-component Castagnoli–cushman Reactions (2c-ccr)mentioning
confidence: 99%
“…Other solvents have also been used, resulting in different proportions of diastereoisomers [ 29 ]. In some cases, the reaction takes place at room temperature, preferentially yielding the cis isomers [ 30 , 31 , 32 , 33 ]. Trifluoroethanol has proven to be an advantageous solvent for the CCR, allowing a variety of lactams with high diastereoselectivity for cis -kinetic diastereoisomers to be obtained in minutes at −40 °C [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…They represent promising drugs with potentially fewer side effects. It is proposed that the new chemical will have a multi-mechanism of action like nuclear receptors targeting, TOP-2 interaction, modulating estrogen receptors, and manipulating VEGFR and HIF-1 alpha [40]. Studies suggested that indenoisoquinolines are weak TOP-1 inhibitors in combination with other functions.…”
Section: Topoisomerase-1 Inhibitors and Cancer Colonmentioning
confidence: 99%